2017
DOI: 10.1016/j.disc.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

On the cop number of generalized Petersen graphs

Abstract: We show that the cop number of every generalized Petersen graph is at most 4. The strategy is to play a modified game of cops and robbers on an infinite cyclic covering space where the objective is to capture the robber or force the robber towards an end of the infinite graph. We prove that finite isometric subtrees are 1-guardable and apply this to determine the exact cop number of some families of generalized Petersen graphs. We also extend these ideas to prove that the cop number of any connected I-graph is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…We intend to demonstrate that three cops do not have a winning strategy on the graphs we are studying. Together with the upper bound of [1], this is sufficient to show that the cop number for these graphs is 4. In order to prove that three cops do not have a winning strategy, we will first show that if three cops have not already trapped the robber, the robber always has a legal move whereby the cops cannot trap the robber on the cops' next move.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…We intend to demonstrate that three cops do not have a winning strategy on the graphs we are studying. Together with the upper bound of [1], this is sufficient to show that the cop number for these graphs is 4. In order to prove that three cops do not have a winning strategy, we will first show that if three cops have not already trapped the robber, the robber always has a legal move whereby the cops cannot trap the robber on the cops' next move.…”
Section: Resultsmentioning
confidence: 91%
“…In [1], Ball et al showed that the cop number of every generalised Petersen graph is at most 4. They also provided a list of all generalised Petersen graphs with n ≤ 40 that attain this bound.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on generalized Peterson graphs in this paper, although our main result applies to any cubic graph of girth 8. In [1] the analysis was extended to I graphs. They proved that the cop number of a connected I-graph I(n, k, j) is less than or equal to 5.…”
Section: Previous Researchmentioning
confidence: 99%
“…For some families that do not have girth 8, the cop number is already known, or tighter bounds have been found. For example, when k = 1, GP (n, 1) has a girth of 4, and its cop number is known to be 2 [1]. Likewise, when k = 3 the girth is 6 (except for some small values of n) and the cop number is known to be at most 3 [1].…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation